1993
DOI: 10.1002/ijc.2910530409
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated allelic losses in the development of invasive urothelial cancer

Abstract: To investigate the roles of allelic loss in the development of urothelial cancer, loss of heterozygosity was examined on 7 chromosomal arms in 49 cases of urothelial cancer of various grades and stages. Loss of heterozygosity was found in alleles in order of frequency as follows: 9q (21/38, 55%), 11p (20/44, 45%), 17p (18/42, 43%), 13q (10/39, 26%), 3p (8/41, 20%), 10q (2/29, 7%), and 1p (1/36, 3%). Invasive (high-grade or > or = pT2) tumors showed the loss of 17p (13/16, 81%) and the loss of 13q (7/16, 44%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
1
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 20 publications
(26 reference statements)
3
47
1
1
Order By: Relevance
“…Deletion of chromosome 10 has been observed in cytogenetic studies of bladder cancer (Sandberg 1994), mostly as monosomy but in some cases as speci®c deletion of 10q. Loss of heterozygosity on chromosome 10q has previously been reported in 5 ± 7% of bladder tumors (Knowles et al, 1994;Habuchi et al, 1993) and 29% of renal tumors in allelotype studies (Morita et al, 1991a).…”
mentioning
confidence: 89%
“…Deletion of chromosome 10 has been observed in cytogenetic studies of bladder cancer (Sandberg 1994), mostly as monosomy but in some cases as speci®c deletion of 10q. Loss of heterozygosity on chromosome 10q has previously been reported in 5 ± 7% of bladder tumors (Knowles et al, 1994;Habuchi et al, 1993) and 29% of renal tumors in allelotype studies (Morita et al, 1991a).…”
mentioning
confidence: 89%
“…More than 60% of transitional cell carcinomas (TCC) of the bladder of all stages and grades show loss of heterozygosity (LOH) of chromosome 9. [1][2][3][4][5][6] Although many tumors have LOH on both arms of the chromosome, a significant number (ϳ10% of tumors overall) have a region of interstitial LOH of 9p. 7 Many such deletions are small and this has allowed the identification of a critical region at 9p21 that contains CDKN2B and CDKN2A/ARF.…”
mentioning
confidence: 99%
“…Cytogenetic and molecular studies have identified genetic alterations on chromosome 11p as one of the most frequent events during the progression of bladder cancer (Habuchi et al, 1993;Shaw and Knowles, 1995;Voorter et al, 1996;Gibas and Gibas, 1997). Deletion mapping has revealed a common region of deletion between D11S922 (11p15.5) and D11S569 (11p15.1-11p15.2), but it is not yet known which particular gene constitutes the relevant target.…”
mentioning
confidence: 99%